Exploring the relationship between English language syntax and cohesion in professional discourse - Roozafzai, Zahra Sadat (Politeknik Negeri Jember, 2025)
This study explores the relationship between English language syntax and cohesion in professional discourse across domains such as business, law, medicine, and academia. Using a mixed-methods approach, the research combines quantitative corpus analysis of syntactic structures and cohesive devices with qualitative discourse analysis guided by Hallidayan Functional Grammar. The study analyzes 200 authentic professional texts, sourced from academic databases, institutional repositories, and public domain documents, ensuring a comprehensive and representative sample. Findings reveal that syntactic structures and cohesive devices play crucial roles in shaping textual coherence and comprehension. For instance, coordination establishes hierarchical relationships between clauses, while ellipsis helps maintain consistency by omitting redundant information. However, complex syntactic structures often hinder comprehension, particularly for non-native speakers. A comprehension study conducted with 120 participants (60 native and 60 non-native English speakers) further supports these findings. Native speakers outperformed non-native speakers across all conditions, but both groups benefited significantly from high levels of cohesive devices, particularly in texts with simpler syntax. Statistical analysis using ANOVA shows a significant interaction between syntactic complexity and cohesive devices (p = 0.05), underscoring the importance of balancing these linguistic features. This research contributes to the fields of linguistics, professional communication, and discourse analysis by identifying patterns and correlations that enhance understanding of professional texts.